Contemporary Hit Radio as a format of radio stations-leaders in radio broadcasting - Arsenteva, Galina L. (Opción, 2019)
The paper discusses one of the two radio format groups which are the most popular in Russia, namely, Contemporary Hit Radio (CHR) via theoretical and general scientific methods. In particular, using the methods of analogy and generalization, conclusions were made regarding the reasons for the popularity of this group of formats and the peculiarities of CHR in Russia were identified. The main conclusion of the study is based on the assumption that the radio stations of the CHR format group are by many parameters included in the top radio stations of Russia, including advertising volume and audience size.